(872) Lectures on manpower planning محاضرات حول تخطيط القوى العاملة - E.Stiller.; M.Mongi. (INP, 2024)
The lectures on manpower planning cover a range of general fundamentals and methodological principles. They include the targets and contents of manpower planning, where target functions are determined and strategic concepts are developed. The content also addresses the analysis of manpower structure, inventory estimation, and demand, along with an analysis of the initial situation and planning methods. Additionally, it discusses the development of theory and practice of manpower planning in the German Democratic Republic (GDR). At the national level, the analysis and forecasting of total manpower development include the volume of total manpower, regional structure, socio-economic structure, sectoral structure, and qualification structure. The planning system for national total manpower encompasses the relationship between sectoral and regional structures, as well as the connection between manpower demand and the educational system. The lectures also review experiments with planning models, including the construction of a static model for calculating manpower inventory with illustrative examples.